Answers

2015-02-26T23:11:58+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
If -2 is the root of the equation x² + 7x + k = 0; then
(-2)² + 7×(-2) + k = 0
⇒ 4 - 14 + k = 0
⇒ -10 + k = 0
k = 10

the equation is x² + 7x + 10 = 0. 
let the other root is β.
we know that sum of roots is -b/a, that is -7/1 = -7.
⇒ β + (-2) = -7
⇒ β - 2 = -7
⇒ β = -7 + 2 
⇒ β = -5
So other root is -5.
0
2015-02-27T12:01:42+05:30
One root of x²+7x+k = 0 is -2
therefore, (-2)² + 7(-2)+k = 0
4 - 14 + k = 0 
k = 10

The equation is x²+7x+10 = 0

Product of the roots = αβ = 10
(-2) β = 10
β = -5
the other root is -5
0